أثر آليات حوكمة الشركات على تضييق فجوة التوقعات في المراجعة من وجهة نظر المراجعين الخارجيين(دراسة ميدانية على بيئة المراجعة الليبية). (Economic studies journal, 2018)
The study aims at identifying the impact of corporate governance mechanisms on narrowing the expectations gap in auditing in Libya. The study is based on the analytical descriptive approach through the design of a questionnaire distributed to the sample of the study, which was represented by the external auditors and the staff of the Audit Bureau in the cities of Sirte and Misratah. A number of statistical methods were used, the most important of which are the arithmetical averages, standard deviations, (T test) to examine the hypothesis, and Cronbach's Alpha to examine the credibility of data. The main findings of the study are: The governance mechanisms of uncertainty about the independence of the external auditor, the auditor's compliance with audit standards and guidelines, the poor performance of the external auditor in auditing, the mandatory change and the uncertain role of the external auditor and his responsibilities, the extent of consulting services provided by the auditor to the audited company, and the relationship between the company administration and the external auditor, affect the narrowing of the expectations gap in auditing.
Keywords: Governance Mechanisms; The Expectations Gap; Auditing in Libya; External Auditors